PERSEPSI PESERTA DIDIK TERHADAP PERILAKU BERPACARAN DIKELAS XII SMA KRISTEN ABDI WACANA PONTIANAK - Alda, Veronika; Yuline, Yuline; Putri, Amallia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to determine students"™ Perceptions of dating behavior in class XII at SMA Kristen Abdi Wacana Pontianak positively and negatively. The research method used in this thesis is a descriptive method with a quantitative research form. The data sources in this study were students in class XII SMA Kristen Abdi Wacana Pontianak and the entire study population, totaling 28 students, used a questionnaire as a data collection tool. The results showed that the perception of dating positively by 53,21% was included in the very low category which could be interpreted as students"™ understanding of positive dating behavior that was still not properly understood and the perception of dating negatively by 56,81% was included in the very low category. Which means that most of the students"™ understood about what dating behavior is like. So it can be concluded that students"™ perceptions of dating behavior in Class XII SMA Kristen Abdi Wacana Pontianak still need more in-depth education about dating behavior both positively and negatively.